Determinants of financial inclusion and adoption of Islamic Banking : evidence from Mauritania - Sidi, Mohamed (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2021)
It has been globally acknowledged that financial inclusion (FI) is one of the most important pathways to achieve sustainable development and reduce the incidence of poverty in society. However, not less than 50% adults in low-income segments are still financially excluded all over the world. Demographic factors, as well as other relevant factors such as financial literacy, religion, location, and cost of financial services are among the most significant determinants of financial inclusion globally as discussed in the literature review. Therefore, the general aim of this study is to investigate factors and barriers of FI, and the potential role of Islamic banking in tackling financial exclusion in the case of Mauritania. The specific objectives are (1) to investigate the driving forces that influence financial inclusion in Mauritania; (2) to investigate the driving forces that influence people’s intention to adopt Islamic banking in Mauritania; (3) To assess the moderate effects of socioeconomic and demographic factors on the relationships between attitude, subjective norms, and perceived behavioural control, with behavioural intention towards adopting Islamic banking in Mauritania; (4) to provide policy recommendations based on the results and enhance the inclusion within Islamic banking that can help Mauritanians to be financially included. The importance of this research is that it is the first of its kind in Mauritania and it includes several cities and various stakeholders as well as using multiple econometric methods. The non-probability sampling technique is used for gathering primary data through structured questionnaires from three Mauritanian cities, namely Nouakchott, Nouadhibou, and Kiffa. Exactly 800 questionnaires were distributed; however, only 583 were usable in the analysis. The research objectives of this study were achieved by using different statistical methods. Logistic regression analysis was used to answer RQ1, whereas Structural Equation Modeling (SEM) and Multi Group Analysis (MGA) were used to answer RQ2, RQ3, and RQ4. The result shows that educational level, income, employment status, religious factors, financial cost, and financial education are proven to influence financial inclusion in Mauritania. In the context of behaviour towards Islamic banking, it is proved that attitude, subjective norms, and perceived behavioural control significantly and directly affect behavioural intention towards adopting Islamic banking. Further, awareness of Islamic banking and finance, geographical factors, religious factors, financial cost, and financial education are proven to have indirect influence on behavioural intention. Meanwhile, actual behaviour towards accessing Islamic banking and finance were found to be significantly and directly influenced by behavioural intention. Socioeconomic and demographic factors are found to have moderating effects on all direct paths towards behavioural intention. This study suggests that the first priority for policy makers should be the designing of a specific financial inclusion strategy to stem the negative tide of exclusion taking into consideration the outcome of this study. Secondly, financial education should include Islamic finance courses to enhance the level of awareness of finance and Islamic finance in formal education. Third, government should promote Islamic banking as an alternative to conventional banking, taking into consideration all factors and barriers referred to in this study. Finally, the study mainly contributes to the practical and theoretical aspects of tackling financial exclusion.